PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI SULAWESI TENGGARA : indonesia - Muhammad Nur Afiat; Zainuddin Saenong; Puspa Dewangga (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study was conducted with the aim to know the influence of Human Development Index (HDI) and Economic Growth Against Unemployment Rate in Southeast Sulawesi Province Year 1996-2018. This research is a type of quantitative research using secondary data in the form of time series data from 1996-2018. Source of data obtained from the Central Bureau of Statistics (BPS) of Southeast Sulawesi Province. This research also use multiple linear regression analysis tool with ordinary least square method (OLS) and then processed by application of Eviews 8.0. The result of research indicate that (partial) the Human Development Index (IPM) has significant influence to the level of unemployment in Southeast Sulawesi Province. Then Economic Growth has significant influence to the Human Development Index (IPM). Result of F test show value of probability (F-statistic) that is 0.000034 <0,05. This means that simultaneously Human Development Index (HDI) and Economic Growth have significant effect on Unemployment Rate in Southeast Sulawesi Province 1996-2018